227k views
4 votes
Solve the equation. x^2 − 6x − 7 = 0

A) x = 7
B) x = 1
C) x = 1 or x = −7
D) x = −1 or x = 7

User AndrewVos
by
5.6k points

2 Answers

5 votes

Answer:

D

Explanation:

given x² - 6x - 7 = 0 ← in standard form

To factor the quadratic

Consider the factors of the constant term ( - 7 ) which sum to give the coefficient of the x- term ( - 6)

The factors are - 7 and + 1, since

- 7 × 1 = - 7 and - 7 + 1 = - 6, thus

(x - 7)(x + 1) = 0 ← in factored form

Equate each factor to zero and solve for x

x - 7 = 0 ⇒ x = 7

x + 1 = 0 ⇒ x = - 1

The solution to the equation is D

User Chandrahas Balleda
by
5.0k points
6 votes

x equals 7,-1 :)))))))))))

User Jlang
by
5.4k points